2003
DOI: 10.1055/s-2003-38316
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology Hypotheses and Treatment of Pulmonary Sequestration

Abstract: Illustrated by this case report, partial obstruction of the venous collector of extrapulmonary sequestration explains pleural effusion and fetal hydrops. Therapy requires fetal thoracentesis and neonatal arterial occlusion of the pedicle artery allowing uneventful follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Some suggest that overcirculation through the sequestrated lung may induce congestive heart failure with resulting hydrops67, while others have raised the possibility of twisting of the vascular pedicle resulting in obstruction of the venous and lymphatic drainage68. The latter hypothesis has recently been verified in a case report69. Postnatal arterial occlusion of the pedicle of a systemic artery led to resolution of lung hyperechogenicity.…”
Section: A Unified Concept For Congenital Lung Malformation and Its Cmentioning
confidence: 98%
“…Some suggest that overcirculation through the sequestrated lung may induce congestive heart failure with resulting hydrops67, while others have raised the possibility of twisting of the vascular pedicle resulting in obstruction of the venous and lymphatic drainage68. The latter hypothesis has recently been verified in a case report69. Postnatal arterial occlusion of the pedicle of a systemic artery led to resolution of lung hyperechogenicity.…”
Section: A Unified Concept For Congenital Lung Malformation and Its Cmentioning
confidence: 98%
“…If this hypothesis is correct, detection of significant venous flow in a large EPS may have a favorable prognostic value. Furthermore, fetal intervention to achieve a cessation of arterial blood flow may salvage the fetus and be a definitive treatment without a postnatal resection [9,10]. Our observations need to be confirmed by further studies on venous circulation of EPS associated with fetal hydrops.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, partial obstruction of the venous system between the aorta and the vertebrae was reported as a cause of PE in one case report [9]. A large EPS with a feeding artery roughly equal in size to the aorta can be without PE or lymphatic channel dilatation, suggesting that excessive flow alone does not always lead to PE production [8].…”
Section: Discussionmentioning
confidence: 99%
“…Morville et al [9] , using angiography, demonstrated a partial obstruction of the aberrant venous system between the aorta and the vertebrae in a neonate with EPS. They postulated that the increased venous pressure, combined with high blood flow in the aberrant artery, resulted in a hyperechogenic lung, blood extravasation into the interstitial space, and eventually pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is not difficult to detect aberrant venous flow around the aberrant artery if there is any flow. In the future, minimally invasive arterial occlusion [10] may become the definitive treatment for a fetus with EPS and massive pleural effusion, making the postnatal resection of EPS unnecessary [5,9,11] .…”
Section: Discussionmentioning
confidence: 99%